Plan Wake up Library Muara Pinang High School Electronics 1 - Lendy Rahmadi; Agustian Prakarsya; srirahayu nilawati (PT. Altaf Publishing Corp, 2024)
The library of SMA Negeri 1 Muara Pinang is one of them facilities provided by SMA Negeri 1 Muara Pinang for help his students​​ in grabbed performance . Library the provide a number of collection very useful books​​ for his students .​ The Library of SMA Negeri 1 Muara Pinang is expected can develop so that students​ feel comfortable For visit to library , yes serves 10 - 30 books transaction during break time , do book data entry new , implemented system​ Now still very manual, because every visitors who will borrow book must write identity book , visitors should too fill in book transaction borrowing as well as return book . In searching book data is also needed thoroughness and quite a long time because must One one by one looking on the shelves books.Library with digital concept (e-library) can be one​ solution For overcome problems that exist in the library normal . With it was built design get up library electronic (e-library), then can repair problem problem the . In the e-library there are: a database that can used For storing book data , besides The database is also useful for the search process book . Based on problem the author​ mean For make design get up library electronic (E-library) for petrified makes it easier management data collection books , services and manufacture report